Freezing Tolerance of Thermophilic Bacterial Endospores in Marine Sediments - Cramm, Margaret A.; Chakraborty, Anirban; Li, Carmen; Ruff, S. Emil; Jørgensen, Bo Barker; Hubert, Casey R. J. (Frontiers in Microbiology, 2019)
Dormant endospores of anaerobic, thermophilic bacteria found in cold marine sediments offer a useful model for studying microbial biogeography, dispersal, and survival. The dormant endospore phenotype confers resistance to unfavourable environmental conditions, allowing dispersal to be isolated and studied independently of other factors such as environmental selection. To study the resilience of thermospores to conditions relevant for survival in extreme cold conditions, their viability following different freezing treatments was tested. Marine sediment was frozen at either -80°C or -20°C for ten days prior to pasteurization and incubation at +50°C for 21 days to assess thermospore viability. Sulfate reduction commenced at +50°C following both freezing pretreatments indicating persistence of thermophilic endospores of sulfate-reducing bacteria. The onset of sulfate reduction at +50°C was delayed in -80°C pretreated microcosms, which exhibited more variability between triplicates, compared to -20°C pretreated microcosms and parallel controls that were not frozen in advance. Microbial communities were evaluated by 16S rRNA gene amplicon sequencing, revealing an increase in the relative sequence abundance of thermophilic endospore-forming Firmicutes in all microcosms. Different freezing pretreatments (-80°C and -20°C) did not appreciably influence the shift in overall bacterial community composition that occurred during the +50°C incubations. Communities that had been frozen prior to +50°C incubation showed an increase in the relative sequence abundance of OTUs affiliated with the class Bacilli, relative to unfrozen controls. These results show that freezing impacts but does not obliterate thermospore populations and their ability to germinate and grow under appropriate conditions. Indeed the majority of the thermospore OTUs detected in this study (21 of 22) could be observed following one or both freezing treatments. These results are important for assessing thermospore viability in frozen samples and following cold exposure such as the very low temperatures that would be encountered during panspermia.